Le concept linguistique d'opérativité - Bidaud, Samuel, Henri (Univerzita Palackého v Olomouci, 2019)
The concept of operativity is fundamental for modern and contemporary linguistics. However, its genealogy, its main principles, and its possible applications to other fields have not been explored until now. This book shows at first to which extent the notion of operativity is central to three main linguistic theories of the 20th century: the Psychomechanics of Language of Gustave Guillaume, the Structural Syntax of Lucien Tesniere, and the Transformational Generative Grammar of Noam Chomsky.
Keywords: Jazyky